2016
DOI: 10.1016/j.ygeno.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

COPD subtypes identified by network-based clustering of blood gene expression

Abstract: One of the most common smoking-related diseases, chronic obstructive pulmonary disease (COPD), results from a dysregulated, multi-tissue inflammatory response to cigarette smoke. We hypothesized that systemic inflammatory signals in genome-wide blood gene expression can identify clinically important COPD-related disease subtypes, and we leveraged pre-existing gene interaction networks to guide unsupervised clustering of blood microarray expression data. Using network-informed non-negative matrix factorization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 43 publications
1
63
0
Order By: Relevance
“…Genetic variations in the cluster on chromosome 15, encoding the nicotinic acetylcholine receptor subunits (CHRNA5-CHRNA3-CHRNB4), are correlated with tobacco addiction and increased risk of COPD, peripheral artery disease, lung cancer and obesity [6,7,8]. Different studies on lung tissue and peripheral blood identified increased expression of genes related to inflammatory pathways and immune regulation [9]. More studies are warranted to recognize those genes and pathways occurring in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations in the cluster on chromosome 15, encoding the nicotinic acetylcholine receptor subunits (CHRNA5-CHRNA3-CHRNB4), are correlated with tobacco addiction and increased risk of COPD, peripheral artery disease, lung cancer and obesity [6,7,8]. Different studies on lung tissue and peripheral blood identified increased expression of genes related to inflammatory pathways and immune regulation [9]. More studies are warranted to recognize those genes and pathways occurring in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, a higher BMI was associated with a cluster that had higher mortality and inflammation [25] as well as overall comorbidity burden [26]. Yet, another study using gene interaction networks to define COPD clusters based on inflammation-influenced genetic profiles showed no significant difference in BMI across groups [27]. Our path analysis also shows conflicting data with BMI having both a negative and an indirect positive relationship with emphysema progression.…”
Section: Discussionmentioning
confidence: 62%
“…The resulting contingency table is subsequently used to quantify the enrichment level (by computing the log odds ratio) and testing enrichment (by a chi-squared test or a Fisher's exact test) for a particular gene set. This method has also been widely applied in the recent literature of genomics and complex disease studies (Richiardi et al, 2015;Walter et al, 2015;Chang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%